The tooth book - LeSieg, Theo., 1904-; Mathieu, Joseph; Seuss, Dr. (New York : Random House, 2003)
Rhyming text and illustrations briefly point out what animals have teeth, their uses, and how to care for them.
On board pages.
Keywords: Teeth -- Fiction; Stories in rhyme